2011
DOI: 10.1007/s11274-011-0985-y
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of methyl parathion hydrolase from Burkholderia cepacia capable of degrading organophosphate insecticides

Abstract: Methyl parathion hydrolase (MPH) from a methyl parathion-degrading Burkholderia cepacia indigenous to Thailand was purified to apparent homogeneity by three steps of column chromatography using Resource S, Sephadex G100, and Octyl Sepharose 4FF columns. Its molecular mass was determined to be 35 kDa, and the pI to be 8.5. The recombinant plasmid pGT1, containing the MPH-encoding gene, mpdB, cloned into pGEX-4T-2 was over-expressed in Escherichia coli as GST-MPH fusion protein. The recombinant MPH was purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Soluble OpdA has been shown to have an apparent melting temperature of 62°C; however, activity rapidly decreased after 55°C (10). No structural or stability data are currently available for OpdA from A. radiobacter; however, other similar phosphotriesterases have been shown to be stable up to 50°C and between pH 6.0 and 10.0 (31,32). The isoelectric points of BLA and NanA are 6.9 and 4.5, respectively (27,29), while the isoelectric point of a well-characterized homologous phosphotriesterase from Brevundimonas diminuta is 8.3 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble OpdA has been shown to have an apparent melting temperature of 62°C; however, activity rapidly decreased after 55°C (10). No structural or stability data are currently available for OpdA from A. radiobacter; however, other similar phosphotriesterases have been shown to be stable up to 50°C and between pH 6.0 and 10.0 (31,32). The isoelectric points of BLA and NanA are 6.9 and 4.5, respectively (27,29), while the isoelectric point of a well-characterized homologous phosphotriesterase from Brevundimonas diminuta is 8.3 (33).…”
Section: Discussionmentioning
confidence: 99%
“…There is a report in B. cepacia of the mpd gene coding for methyl parathion hydrolase, which is responsible for the hydrolysis of MP (Ekkhunnatham, Jongsareejit, Yamkunthong, & Wichitwechkarn, ). Vikram et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is a report in B. cepacia of the mpd gene coding for methyl parathion hydrolase, which is responsible for the hydrolysis of MP (Ekkhunnatham, Jongsareejit, Yamkunthong, & Wichitwechkarn, 2012). Vikram et al (2012) found in the Burkholderia strain SJ98 genes encoding monooxygenases responsible for the degradation of aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…and Burkholderia sp. [107][108][109][110][111][112]. MPH does not share any sequence similarity to OPHs such as PTE or OpdA.…”
Section: Methyl Parathion Hydrolase (Mph)mentioning
confidence: 99%